Dietary supplement and drug use and doping knowledge and attitudes in Italian young elite cyclists - Loraschi, A.; Galli, N.; Cosentino, M. (Clinical Journal of Sport Medicine, 2014)
Objective: To explore use and attitudes toward drugs and dietary supplements (DS) and knowledge concerning doping in cycling. Design: Retrospective cross-sectional study. Setting: Professional cycling. Participants: Elite under-23 male cyclists. Intervention: Anonymous semistructured questionnaire administered during race periods. Main Outcome Measures: Use and attitudes toward DS and drugs, and doping knowledge. Results: Forty cyclists aged 19 to 23 years and practicing for 14 to 30 h/wk were interviewed. Previous use (last 3 months) of drugs or DS occurred in 33 of 40 (82.5%) and 39 of 40 (97.5%) cyclists, respectively. Almost all the subjects named at least 1 doping agent (range, 1-10). Within a fixed list of 18 substances (among which only 14 were doping agents), participants recognized 3 to 18 of them as doping agents. They recognized tramadol and sildenafil as doping agents, which are not doping agents, and failed to recognize probenecid and albumin, which actually are. Doping knowledge correlated with drug use (r2 = 0.1614; P = 0.01). Participants deemed doping prevalence high among cyclists in general but not in their own team (P < 0.0001). Conclusions: Use of prescription drugs and DS was a common occurrence. Doping knowledge was poor and biased, and its relationship with drug use deserves consideration. Educational interventions are needed to improve knowledge and awareness about prescription drugs and DS use, as well as about doping.